Depth and temperature profiles reflect individual differences in the daytime diving behaviours of pelagic thresher sharks - Oliver, Simon P.; Grothues, Thomas M.; Mayo, Zoe J.; Williams, Amie L.; Silvosa, Medel; Cases, Gary (Frontiers in Marine Science, 2023)
We used acoustic telemetry to investigate the roles of depth and temperature in the daytime foraging behaviours of 13 tagged pelagic thresher sharks by monitoring their fine scale vertical movements in the Philippines. Cumulatively, pelagic thresher shark dives traversed the entire water column where they encountered temperatures that ranged from 33°C at the surface to 12°C at 250 m depths throughout the day, but the movements of individuals varied in the extent of both their deep and shallow water limits. Dives were not synchronized to diurnal cycles, and periodicity reflected cycles of similar dives, the dives themselves, deviations, cruising, and individuality. Pelagic thresher shark movements between the warm surface layer and cooler waters below the thermocline (155 – 175 m) may reflect a common Alopiid strategy that balances maintaining tolerable ambient water temperatures with opportunities to search for and forage on spatially patchy distributions of prey.